1986
DOI: 10.1530/acta.0.1110336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pregnancy hormones on pancreatic islets in organ culture

Abstract: Pregnancy is associated with hyperinsulinaemia and decreased glucose tolerance which may lead to gestational diabetes. Sera from pregnant women in the last trimester were found to stimulate insulin secretion of mouse pancreatic islets maintained in organ culture suggesting a direct effect of pregnancy hormones and/or metabolites on the endocrine pancreas. Previous studies have shown that progesterone and human placental lactogen (hPL) had direct effects on isolated islets and in the present study the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 15 publications
(20 reference statements)
1
13
1
1
Order By: Relevance
“…of these gonadal factor(s) might also explain the discrepancy between the stimulation of islet-cell proliferation by progesterone in vivo, as shown in the present study, and the inhibitory effects of progesterone on islet-cell proliferation in vitro (12)(13)(14), under which conditions such factors are absent.…”
Section: Discussioncontrasting
confidence: 50%
“…of these gonadal factor(s) might also explain the discrepancy between the stimulation of islet-cell proliferation by progesterone in vivo, as shown in the present study, and the inhibitory effects of progesterone on islet-cell proliferation in vitro (12)(13)(14), under which conditions such factors are absent.…”
Section: Discussioncontrasting
confidence: 50%
“…Studies of 3H-thymidine incorporation into new¬ born rat islets have shown that progesterone is inhibitory in a concentration of 1 pg/ml (Nielsen et al 1981). Neither oestradiol nor testosterone had any effect (unpublished observation) in agreement with the unchanged DNA content in mouse islets cultured in the presence of the hormones (V).…”
Section: Effects On Islet Growthsupporting
confidence: 56%
“…However, acute experiments on isolated rat islets have failed to show any effect (see Malaisse 1972). In contrast to the effect of hydrocortisone (IV), there was no inhibitory effect of progesterone when the concentration was in¬ creased from 0.1 µg/ml (5 x 10~7 mol/1) to 1 µg/mI (5 x 10-6 mol/1) (Nielsen et al 1981). By the same arguments as above the employment of longterm culture of mouse islets with sub-optimal sup¬ plement of serum (section 4.1) offers a useful approach to study chronic stimulatory effects, and has thus confirmed the stimulatory effect of pro¬ gesterone (V).…”
Section: Effects On Insulin Releasementioning
confidence: 84%
“…In order to maintain glucose homeostasis the endocrine pancreas undergoes structural and functional changes, including increased glucose-induced insulin secretory responses (Green & Taylor 1972, Moes et al1988, increased synthesis (Bone & Taylor 1976) and storage (Dunger et al 1989) of insulin, b-cell hypertrophy (Hellman 1960, Aerts & Van Assche 1977, Dunger et al 1989) and hyperplasia caused by enhanced b-cell proliferation (Hellman 1960, Aerts & Van Assche 1977. It has been suggested that gestational hormones are involved in these changes, as in vitro hormones of the placental lactogen (PL)-growth hormone (GH)-prolactin (Prl) family induce increased insulin production and release as well as increased cell proliferation in islets of Langerhans (Nielsen 1982, Sorenson & Parsons 1985, Nielsen et al 1986, Parsons et al 1992. Still, gestational hormones are not likely to be the only factors in£uencing endocrine pancreas function during pregnancy.…”
mentioning
confidence: 99%